Molecular Study Using Real Time PCR to Detect Influenza Viruses (Flu A, Flu B and RSV) in Patients at Ramadi Hospital - Abbas O. Al.janabi; Mohammed Amer Fayyadh; Aseel Khalid Hameed; Najeeb Mohammed Hussein (Indian Journal of Forensic Medicine & Toxicology, 2022)
Background: Because of the increasing incidence of infections with different types of influenza ofvarious types, type A, B, and SRV, this study included investigating the type of infection in influenzain women and men in different age groups and making a comparison between them. Methodology: 90blood samples were collected, including 30 samples for men 30 samples for women showing clinicalsymptoms of infection, and 30 samples from people with clinical symptoms under control. Thesesamples were placed in tubes containing an anticoagulant to ensure that blood does not clot DNA/RNAextraction kit, CerTest, Spanish Company and detection by Flu A, Flu B and RSV, CerTest, SpanishCompany by using real time PCR. Result: Table 1 shows the investigation of some types of influenzain women who showed symptoms of infection and who are between 20 to 40 years old, where thefrequency of infection in women between the ages of 20-30 years was high with types Flu A, SRVcompared with control and did not show infection with type B for the same Age group . As for womenaged between 30-40 years, the frequency of type B infection was high compared to control, and therewere no infections with Flu a and SRV for the same age group .